Synthesis and Characterization of 2,3-Dioximino-1,2,3,4-tetrahydroquinoxaline Complexes with Co(II), Ni(II), Cu(II), Zn(II), Cd(II), Hg(II) and UO2(VI) - Kakanejadifard, Ali; Toosi-Jamali, Hossein; Ghasemian, Motaleb (Asian Journal of Chemistry, 2010)
A vic-dioxime, 2,3-dioximino-1,2,3,4-tetrahydroquinoxaline, was prepared as a mixture of dichloroglyoxime and 1,2-phenylendiamine (H2L). The mononuclear metal complexes have been synthesized with Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) salts. H2L forms mononuclear complexes [(HL)2M] with a metal ligand ratio of 1:2 with M= Co(II), Ni(II) and Cu(II). Zn(II), Cd(II) and Hg(II) form with H2L complexes [(H2L)MCl2], which have a metal ligand ratio of 1:1. The results indicated that the metal ions are coordinated through the two N atoms of the ligand, as in most of the vicdioximes. H2L forms the dinuclear complex [(H2L)(OH)2M2] and a metal ligand ratio of 1:1 with M = UO2(VI). The composition and the structural formula of the ligand and of the resulted complexes were confirmed by elemental analysis, IR, MS and NMR spectroscopy methods.